Strategic Integration of Lean Construction into Green Building Regulations: A Factor-Based Assessment of Green Construction Indicators - Ferry Firmawan; Lala Anggraini (Advance Sustainable Science Engineering and Technology, 2026)
The construction sector plays a critical role in sustainability through effective construction waste management. In Indonesia, green building practices are guided by the Green Construction Site Index (GCSI) and the Minister of Public Works and Housing Regulation No. 21 of 2021; however, their strategic alignment with Lean Construction principles remains limited. This study examines the strategic integration of Lean Construction into green building regulations by validating regulatory-based indicators using the three Lean Construction pillars: Systems Management, Technology Management, and Culture and Behaviour. A questionnaire survey of construction practitioners was analyzed using Exploratory Factor Analysis (EFA). The results reveal a robust three-factor structure, accounting for 80.1% of the total variance, with Systems Management as the dominant dimension. The findings provide practical insights for strengthening regulatory coherence, improving waste reduction strategies, and enhancing sustainable performance during the construction phase of building projects.